Comparison of intubating conditions at 60 seconds with cisatracurium 4*ED95 dose and cisatracurium 2*ED95 dose plus priming dose and low dose ketamine - Rahul G Daga; Irbinder Kour Bali; Pushparaj Nilkanth Patil; Rohit Ghanshyamdas Daga; Rashmi Daga; G S Devika (Wolters Kluwer Medknow Publications, 2023)
Introduction: To compare the intubating conditions at 60 seconds between 4*ED95 dose of cisatracurium and 2*ED95 dose of cisatracurium in combination with priming and low dose ketamine Primary Objective: jaw relaxation for laryngoscopy, vocal cord position on laryngoscopy, and coughing or bucking response to intubation. Secondary Objective: To compare the hemodynamic changes up 10 minutes after intubation in the two groups. In this prospective study, a total of 68 patients were undergoing general anesthesia for surgery with placement of endotracheal tube placement. Patients will be divided into two groups comprising 34 patients each. The patients were allocated one of the two groups by computerized randomization. *Group A received bolus dose of cisatracurium which is 0.2 mg/kg (4*ED95). **Group B received cisatracurium in dose of 0.1 mg/kg (2*ED95) with priming (which is 10% of the bolus dose) and low dose ketamine of about 0.5 mg/kg. It was possible to achieve acceptable laryngoscopy and intubating condition in both the groups within 90 seconds. When grades of laryngoscopy and ease of intubation were compared, 2*ED95 dose along with priming plus low dose ketamine produced superior results than 4*ED95 group. When the mean arterial pressure and pulse rate were compared between the two groups, it was observed that mean arterial pressure and pulse rate were only slightly higher in the 2*ED95 along with priming and ketamine.